Provoking electrocatalytic activity with bio-molecules at inactive gas diffusion layers. (June 2019) - Ede, Sivasankara Rao; Karthick, Kannimuthu; Kennedy, Jeevarathinam; Kundu, Subrata
Abstract: Developments of earth abundant and highly active metal-free electrocatalysts pave a new way for nurturing economically viable water splitting for hydrogen production. Recent findings showed that deoxyribose nucleic acid (DNA) can be employed to reduce the loading of expensive catalysts like Pt and to increase the catalytic activity of catalysts in the streams of hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR) respectively. Herein, for the very first time, we found an interesting property of DNA in electrocatalysis by a simple and fast physical modification over the gas diffusion layers (GDL). The DNA molecule while embedded over the GDL surface, it has modified the surface phenomenon in addition to the active functional groups to give the electrocatalytic activity. The DNA modified GDL (DGDL) has showed better kinetic trend and activity in both oxygen evolution reaction (OER) and HER in alkaline and acidic media respectively. To further ensure the nature of these surface modified GDL, we have utilized other important bio-molecules also and studied their activity in comparison with DNA. For that, we have chosen carboxymethyl cellulose (CMC) and bovine serum albumin (BSA) bio-molecules for the same. In OER in 1 M KOH, to reach 10 mA cm −2 current density, DGDL required an overpotential of 384 mV compared to CGDL and BGDL which required 402 and 414 mV respectively. Similarly, for HER too, for attaining 10 mA cm −2, DGDL, CGDL and BGDL required overpotentials 298, 369 and 393 mV respectively. The increase in activity was owing to the presence of surface functionalities that facilitated improved charge transfer kinetics and electrode-electrolyte interaction in an efficient manner. With these fruitful findings in activities, in futuristic, our proposed route can be extended to design various other smart, cost effective and self-standing metal free catalysts in a facile way. Graphical abstract: Flexible, self-standing and cost-effective metal-free electrode was fabricated by physical modification of the surface of GDL via simple drop casting of bio-molecules like DNA, CMC and BSA. The fabricated materials showed excellent performance both in HER and OER studies for electro-catalytic water splitting. This highly facile, low cost electrode designing protocol will be a good alternative to the currently pursued complicated practices for devising metal-free catalyst to nurture economically viable water electrolysis.Image 1 Highlights: Surface functionalization of GDL with bio-molecules at lower temperature ( 80 deg C) has been achieved for the first time. All three modified GDL electrodes such as DGDL, CGDL and BGDL shown excellent electro-catalytic activity both in OER &HER. Amongst modified GDL electrodes, the DGDL showed high catalytic activity & excellent stability in alkaline & acidic media. Our catalyst has shown promising activity in HER & OER over other hetero atom doped metal-free catalysts. In futuristic our process could be extended to design various other smart, cost-effective and self-standing catalysts.